Reconstitution fluid type does not affect pulmonary inflammation or DNA damage following infusion of lyophilized plasma. Issue 2 (February 2015) - McCully, Sean P.; Lee, Tim H.; McCully, Belinda H.; Sands, Claire L.; Rick, Elizabeth A.; Dean, Rondi K.; Anderson, Nathan W.; Hampton, David A.; Louis, Scott G.; Differding, Jerome A.; Schreiber, Martin A.
<x xml:space="preserve">Abstract</x> BACKGROUND Dysfunctional inflammation following traumatic hemorrhage can lead to multiple-organ failure and death. In our polytrauma swine model, lyophilized plasma (LP) reconstituted with sterile water and ascorbic acid suppressed systemic inflammation and attenuated DNA damage. However, it remains unknown whether the inflammatory response is affected by the type of fluid used to reconstitute LP. We hypothesized that common resuscitation fluids such as normal saline (LP-NS), lactated Ringer's solution (LP-LR), Hextend (LP-HX), or sterile water (LP-SW) would yield similar inflammation profiles and DNA damage following LP reconstitution and transfusion. METHODS This was a randomized, prospective, blinded animal study. LP was reconstituted to 50% of original volume with NS, LR, HX, or SW buffered with 15-mM ascorbic acid. Forty swine were subjected to a validated model of polytrauma, hemorrhagic shock, and Grade V liver injury and resuscitated with LP. Serum interleukin 6 (IL-6), IL-10, plasma C-reactive protein, and 8-hydroxy-2-deoxyguanosine concentrations were assessed for systemic inflammation and DNA damage at baseline, 2 hours, and 4 hours following liver injury. Lung inflammation was evaluated by Real Time Polymerize Chain Reaction (RT-PCR). RESULTS Reconstituted LP pH was similar between groups before resuscitation. IL-6 and IL-10 increased at 2 hours and 4 hours compared with baseline in all groups (p < 0.017). DNA damage increased at 2 hours and 4 hours compared with baseline and from 2 hours to 4 hours in the LP-NS, LP-LR, and LP-SW groups (all p < 0.017). Animals resuscitated with LP-HX not only demonstrated increased DNA damage at 4 hours versus baseline but also had the lowest C-reactive protein level at 2 hours and 4-hours (p < 0.017). Overall, differences between groups were similar for DNA damage and lung inflammation. CONCLUSION Reconstitution fluid type does not affect inflammatory cytokine profiles or DNA damage following LP transfusion in this swine polytrauma model. Based on universal availability, these data suggest that sterile water is the most logical choice for LP reconstitution in humans. LEVEL OF EVIDENCE Prognostic, level II.